Filmless quality assurance of a Leksell Gamma Knife® Icon™. Issue 1 (10th December 2020) - Maraghechi, Borna; Kim, Taeho; Mitchell, Timothy J.; Goddu, S. Murty; Dise, Joe; Kavanaugh, James A.; Zoberi, Jacqueline E.; Mutic, Sasa; Knutson, Nels C.
Abstract: Purpose: The annual quality assurance (QA) of Leksell Gamma Knife ® (LGK) systems are typically performed using films. Film is a good candidate for small field dosimetry due to its high spatial resolution and availability. However, there are multiple challenges with using film; film does not provide real‐time measurement and requires batch‐specific calibration. Our findings show that active detector‐based QA can simplify the procedure and save time without loss of accuracy. Methods: Annual QA tests for a LGK Icon™ system were performed using both film‐based and filmless techniques. Output calibration, relative output factors (ROF), radiation profiles, sector uniformity/source counting, and verification of the unit center point (UCP) and radiation focal point (RFP) coincidence tests were performed. Radiochromic films, two ionization chambers, and a synthetic diamond detector were used for the measurements. Results were compared and verified with the treatment planning system (TPS). Results: The measured dose rate of the LGK Icon was within 0.4% of the TPS value set at the time of commissioning using an ionization chamber. ROF for the 8 and 4‐mm collimators were found to be 0.3% and 1.8% different from TPS values using the MicroDiamond detector and 2.6% and 1.9% different for film, respectively. Excellent agreement was found between TPS and measured dose profiles using the MicroDiamond detector which was within 1%/1 mm vs 2%/1 mm for film. Sector uniformity was found to be within 1% for all eight sectors measured using an ionization chamber. Verification of UCP and RFP coincidence using the MicroDiamond detector and pinprick film test was within 0.3 mm at isocenter for both. Conclusion: The annual QA of a LGK Icon was successfully performed by employing filmless techniques. Comparable results were obtained using radiochromic films. Utilizing active detectors instead of films simplifies the QA process and saves time without loss of accuracy.